SIMPLE ADDITIVE WEIGHTING IN SELECTION OF CITIES PERFORMANCE OF NON SMOKING AREA AND TOBACCO ADVERTISEMENTS, PROMOTIONS AND SPONSORS BAN - Tazkiyah Herdi; Ardiansyah Dores; Fajar Masya (Bakti Nusantara Institute, 2020)
Decision support system is growing and getting a lot of attention from researchers and practitioners to help evaluate and rank several industrial sectors. Previous researches have implemented a decision support system in various industries, such as the clinical industry, human resources, and others. However, evaluation of the measurement of the implementation level does not yet exist in the implementation of the non-smoking area and tobacco advertisements, promotional, and sponsor ban. To control active smokers, regional governments are supported by the central government issuing regional regulations about Non- Smoking Area and Tobacco Advertising, Promotion and Sponsoring (TAPS). This paper aims to measure the level of implementation of non-smoking area and tobacco advertisements, promotional, and sponsor ban. This study using the integrated survey simple additive weighting method. Integrated survey simple additive weighting is collecting survey data that is integrated with each region and calculates survey results by looking for weighted sums of rating indicators for each alternative on all attributes.